2007
DOI: 10.1186/bf03352050
|View full text |Cite
|
Sign up to set email alerts
|

Interseismic deformation of the Nankai subduction zone, southwest Japan, inferred from three-dimensional crustal velocity fields

Abstract: We have studied crustal deformation in the Nankai subduction zone, southwest Japan, based on threedimensional GPS velocity fields. Oblique subduction of the Philippine Sea plate has caused two different modes of deformation of the overriding plate: interseismic crustal shortening in the direction of plate convergence, and permanent lateral movement of the forearc. The block boundary dividing the forearc is the Median Tectonic Line (MTL); however, we assumed that its shallower portion is fully or partially lock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(28 citation statements)
references
References 22 publications
3
24
1
Order By: Relevance
“…the Nankai in southwest Japan. The Nankai subduction zone is one of the particularly appropriate examples because it has a short recurrence period (100-150 years) and a geodetic/seismological data set spanning almost a complete earthquake cycle (Tabei et al, 2007).…”
Section: Absolute Sea Level Change Of the Period 1940-2004mentioning
confidence: 99%
See 1 more Smart Citation
“…the Nankai in southwest Japan. The Nankai subduction zone is one of the particularly appropriate examples because it has a short recurrence period (100-150 years) and a geodetic/seismological data set spanning almost a complete earthquake cycle (Tabei et al, 2007).…”
Section: Absolute Sea Level Change Of the Period 1940-2004mentioning
confidence: 99%
“…However, they clearly suggest a gradual decrease of vertical velocity in the far field. In the Nankai subduction zone, Tabei et al (2007) used data from an array of CGPS to generate a vertical velocity field of the crustal deformation. The distribution shows that as distance from the trough increases, the rates of vertical motion become less varied.…”
Section: Absolute Sea Level Change Of the Period 1940-2004mentioning
confidence: 99%
“…Recent geodetic observations have revealed that the strength of the locking of the plate interface depends on the depth of the subducting plate. In the Nankai subduction zone, seismogenic subduction faults at a depth of 5–25 km are strongly locked; however, at the transition zone at a depth of 25–35 km, GPS observations revealed that the locking was weaker than that of the shallow plate interface [ Tabei et al , 2007]. …”
Section: Introductionmentioning
confidence: 99%
“…Geodetic observations have revealed that the strength of the locking of the plate interface depends on the depth of the subducting plate. In the Nankai subduction zone, seismogenic faults at depths of 5-25 km are strongly locked, although locking at the transition zone at depths of 25-35 km, where short-term SSEs and nonvolcanic DLF tremors are located, is weaker than at shallow depths (Tabei et al, 2007). A simulation study revealed that the recurrence interval of short-term SSEs becomes short as the occurrence of a great earthquake becomes imminent (Matsuzawa et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Hirose et al (2010) applied this method to the DLF tremors of the Shikoku region of southwestern Japan. They found that the average slip rate compensates for the difference between the convergence rate at the trench (Miyazaki and Heki, 2001) and the slip deficit rate at the transition zone (Tabei et al, 2007) of the subducting Philippine Sea plate.…”
Section: Introductionmentioning
confidence: 99%